Nanašanje tankih plasti s pulznim laserjem - Kek-Merl, Darja (Vakuumist, 2001)
High-power laser pulses can be used to vaporize s small area of the target. Generated cloud of the target material is then deposited onto the substrates. Laser radiation passing through the vapour cloud can also ionize a high percentage of the vapour. The most common laser type is the excimer laser with wavelength from 151-131 nm depending on the selected gas mixture (ArF-193nm, KrF-248nm, XeCl-308nm) or solid Nd:YAG lasers (266-1064nm). Lasers operate in pulses of energy between 0,1 to 1 J per pulse, duration timeis between 5 and 45 ns and commonly used repetition rates of 1 to 100 Hz. This techniques id ideal for the deposition of complex, multicomponent materials like high-temperature superconductors, ferroelectric and ferromagnetic materials.
Keywords: tanke plasti; nanašanje; laserji